Wheat yields variability in Poland at NUTS 2 level in context of production risk - Kobus, Paweł (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2009)
The paper presents an analysis of the wheat yields variability in voivodeships of Poland. The main aim of the study is to present several possible indicators for the crop variability in the context of production risk. It is found that ignoring the long-term yield trends leads to a serious overestimation of production risk.